The Mutual Influence between Chinese and Indonesian Language Users in Sunlie Thomas Alexander’s Short Story “My Mother is a Mong Kap San Woman” - Inayatillah, Fafi; Aziz, Abdul Muhaiminul (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
This article examines how the characters as language users influence one another and what factors enabling or motivating them to do so in Sunlie Thomas Alexander's short story "My Mother is a Mong Kap San Woman". This research uses qualitative approach with discourse analysis method. The narrator and his family members are Chinese Indonesians who speak Hakka language. Their neighbors are Malay people who speak Indonesian language. The narrator, his family, and his neighbors live in Bangka Island, Indonesia. They influence one another using their own certain vocabulary, spelling and articulation while communicating. The findings of this research are education and political repression are the reason for a certain ethnic group not to understand Indonesian language. Nevertheless, this research concludes, the interaction between the two different ethnic groups has created a hybrid language.